Evaluasi Penerapan Sistem Informasi Manajemen Kepegawaian (SIMPEG) di Pemerintah Kota Bogor - Raden Kodarisman; Eko Nugroho (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
SIMPEG is an integrated totality comprisingm rocessing device includes collection, procedures, processing power, and software; storage devices include data center and data bank and communication devices interconnected, dependent, and mutually determine the framework of the provision of information in the field of personnel.This research was to evaluate the implementation of Sistem Informasi Manajemen Kepegawaian (SIMPEG). This research implements information systems model developed [1]. This research was used to test whether the system quality, information quality, and quality service have influence toward the system use and user satisfaction, and also to test whether the system use, user satisfaction dan structure organization have positive influence on net benefits.This research used 60 respondents from SIMPEG users. Data was taken by respondens filled the questionnaires and measured with a Likert scale. Data is analysized by Structural Equation Modelling (SEM) and using software SMARTPLS. Test indicates that system quality and service quality has influence on system usage and user satisfaction, while users satisfaction and organizational has influence on the net benefit (level of significant α = 0.05).